Comparison of Stress Concentration Curves for Different Geometries of Machine Elements Obtained via Simulation and Experimentation - Betancur Gómez, Juan Diego; Hoyos Gómez, Felipe; Osorio Patiño, Daniel; Ardila Marín, Juan Gonzalo; Sierra del Rio, Jorge Andrés (TECCIENCIA, 2017)
The aim, herein, was to prove that the analysis of the stress concentration phenomenon with simulation methods provides results that fit those obtained experimentally, thus, corroborating that simulation is a powerful tool that minimizes costs a nd time in the construction of stress concentrator curves. The experimental curves of stress concentration factors available in the scientific literature can be recreated through simulations, achieving results with low errors. Due to this, geometries were selected with different shape ratios for study; these were developed in the DesingModeler® module of the ANSYS Workbench®, then meshed in the Mechanical® module, and three types of load were applied in their borders: axial force, flexing moment, and torsional moment; these were configured in the StaticStructural® module. After obtaining the maximum force and having calculated the nominal force, these were related by calculating the concentration factor to plot it against the geometric parameter modified during the virtual experimentation. In the end, these were compared with the experimental curves consulted. With the results obtained, it was concluded that it is possible to construct curves of stress concentration factor through simulations, with the same reliability as with conventional experimental methods, but at a lower cost.